2015
DOI: 10.1177/2047487315594087
|View full text |Cite
|
Sign up to set email alerts
|

Data from a nationwide registry on sports-related sudden cardiac deaths in Germany

Abstract: BackgroundProspective national registries examining the incidence and aetiology of sports-related sudden cardiac death (SrSCD) not only in competitive athletes but also in recreational sports participants are uncommon. In May 2012, a prospective registry on SrSCD was installed to examine the incidence and particularly the aetiology of such events in the general population in Germany.MethodsThe registry consists of a web-based platform to record SrSCD cases. Media-monitoring and cooperation with 15 institutes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 26 publications
6
71
1
7
Order By: Relevance
“…Consistent with previous reports,6, 22, 29, 30, 31 the majority of exercise‐related OHCAs among the general population were observed in men. The reasons for these differences between the sexes could not be determined from our data and may result from variations between men and women in exercise participation rates and duration or level of exertion during each exercise session.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous reports,6, 22, 29, 30, 31 the majority of exercise‐related OHCAs among the general population were observed in men. The reasons for these differences between the sexes could not be determined from our data and may result from variations between men and women in exercise participation rates and duration or level of exertion during each exercise session.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, the exercise‐related OHCAs in our study were limited to cardiac arrests occurring during exercise. Previous studies estimated the proportion of cardiac arrests occurring during sports activities as ranging from 66% to 92% of all exercise‐related arrests;6, 22, 30, 31 therefore, the exercise‐related OHCA incidence rate in our study may be an underestimation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, in the same study, HCM was observed 8 times more frequently than ARVC (251 vs. 30 cases). We observed a high number of deaths caused by premature CAD and a low number of cases with ARVC and HCM in our cohort, which is in line with reports from Denmark, Germany, Norway and Ireland [19, 20, 25, 26]. The differences between the aforementioned studies support the theory that regional differences in population characteristics play a central role in the epidemiology of SCD, particularly in athletes [8].…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, in the registry from Germany published in 2015, HCM was identified as a reason in only 5% of athletes. The most common cause of death of athletes under the age of 35 was myocarditis (10). In Italy, that was arrhythmogenic right ventricular cardiomyopathy (23).…”
Section: Etiology Of Scdmentioning
confidence: 99%